The Impacts of a Multifaceted Prenatal Intervention on Human Capital Accumulation in Early Life - Carneiro, Pedro; Kraftman, Lucy; Mason, Giacomo; Moore, Lucie; Rasul, Imran; Scott, Molly (American Economic Review, 2021)
We evaluate an intervention targeting early life nutrition and well-being for households in extreme poverty in Northern Nigeria. The intervention leads to large and sustained improvements in children’s anthropometric and health outcomes, including an 8 percent reduction in stunting 4 years, post-intervention. These impacts are partly driven by information-related channels. However, the certain and substantial flow of cash transfers is also key. They induce positive labor supply responses among women, and enables them to undertake productive investments in livestock. These provide protein rich diets for children, and generate higher household earnings streams long after the cash transfers expire. (JEL I12, I32, I38, J13, J16, J22, O12)